Benefitting from Digital Opportunity: Do Socio-economically Advantaged and Disadvantaged Groups React in the Same Ways?. Issue 4 (2nd October 2019) - Kaba, Bangaly; Meso, Peter
ABSTRACT: This study investigates differences in Internet continued-use intention for socio-economically advantaged and disadvantaged groups in Cote d'Ivoire by comparing their expectancy disconfirmation models. Its findings postulate that use-continuance behavior may be a viable proxy for understanding digital inequality especially in societies where the internet is readily accessible. In so doing, it provides an alternative theoretical framework for understanding and/or investigating the digital divide in various societal contexts in the current era where, because of significant advances in physical access to the internet made possible by mobile telephony and extensive diffusion of the internet, mere access is rapidly declining in value as a clear proxy for the presence, scope and/or intensity of the digital divide. Theoretical and practical implications are also discussed.